Pengaruh OCFR, Leverage, Likuiditas dan Fixed Asset Ratio Terhadap Financial Distress dengan Probabilitas Sebagai Variabel Moderasi (Kasus pada Perusahaan Energi di Indonesia) - Salsabila, Alifia Zulfa; Mudrikah, Saringatun (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
The limited availability of energy has caused energy production in Indonesia to decline, which affects the company's financial condition. This research aims to determine the effect of OCFR, leverage, liquidity, and fixed asset ratio on financial distress with profitability as a moderating variable. This research used secondary data which is financial statements obtained from the company’s official website and www.idx.co.id. The population was energy companies in Indonesia consist of 31 companies. Sampling used purposive sampling technique and selected 23 companies. Data collection used documentation techniques and analysis used descriptive statistical analysis and moderation regression analysis. The results showed that the OCFR, leverage, liquidity, and fixed asset ratio simultaneously affect financial distress. Partially liquidity has a positive effect on financial distress. Fixed asset ratio has a negative effect on financial distress. In addition, the OCFR and leverage have no effect on financial distress. Profitability is able to moderate the relationship between OCFR and liquidity, on financial distress, but profitability is not able to moderate the relationship between leverage and fixed asset ratio on financial distress.